Formulation Design, Development of Gastro Retentive Floating Tablets of Propranolol - Saritha, D. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The present research work was carried out by formulate and evaluate the gastro-retentive floating tablets of propranolol. Materials and Methods: Propranolol HCl is an antihypertensive agent. It is mainly used in the treatment of acute myocardial infarctions. Consequently, the current exploration was to design a gastro-retentive drug delivery system of propranolol using swelling polymer through wet granulation method. All the formulations were evaluated for weight variation, hardness, friability, drug content, and in-vitro dissolution. In this gastro-retentive dosage form using hydroxypropylmethylcellulose-K4M (HPMC-K4M) was prepared to develop a sustain release tablets, which could retain in the stomach for longer periods of time delivering the drug to the site of action that is in the stomach. Statistical Analysis used: Fourier-transform infrared signifying compatibility of the drug and polymers in the tablet composition. Results: Pre- and Post-compression parameters of all the formulations were within the pharmacopoeial limits and in-vitro drug release of F2 formulation was found to be 99.14% in 12 h. Conclusion: Dissolution studies of the composition, it was concluded that the formulation F2 which is containing 50 mg of HPMC-K4M, 25 mg of sodium bicarbonate, 25 mg of polyvinylpyrrolidone K30, 1.5 mg of magnesium stearate, and 1.5 mg of Talc is the best formulation. F2 possessed quick buoyancy lag time of 40 s and good total floating time of 12 h. As the consequence of this study, it may accomplish that the floating tablets using HPMC-K4M are a hydrophilic polymer increases the gross register tonnage of the dissolution fluid in the stomach to deliver the drug in a sustained manner.